Kellogg on Biotechnology: Thriving Through - Alicia Loffler [ Editor ] (Kogan Page, 2005)
Publisher description: Biotechnology is the new capital. The stakeholders in this revolution are many: the scientists who generate the knowledge in fields where the pace is maddeningly fast; the technologists who make ideas a reality; the managers who struggle to deal with an industry where the old rules of thinking do not always apply; the venture capitalists who provide funds based on market moods rather than science; the health care, agricultural, chemical, and pharmaceutical industries whose once cozy enclaves have been revolutionized and are now barely recognizable; the law professionals and ethicists who have to grapple with issues unimaginable just a few years ago; the public policy makers who struggle with the complex issues and have to make decisions quickly, or risk being left behind; and, finally, the society and individuals who are in the midst of all that is taking place. This book addresses this diverse constituency and offers an integrated view of exciting new biotechnologies, both from a science and business perspective. The book walks the reader through the "what"--What are some of the newest biotechnologies that will revolutionize the way we think about health?; the "how"--how to transform those technologies into profitable products and companies; and the "who"--who will benefit from these technologies? Kellogg on Biotech is the outgrowth of a collaborative student-faculty effort called TechVentures at the Kellogg School of Management. Their research forms the raw material for Kellogg on Biotech.